Kompetisi Bahasa dalam Industri Kesehatan: Kajian Lanskap Linguistik Papan Nama Apotek di Kecamatan Muncar dan Cluring - Ali Manshur; Mohd Bahaudin Ihsan; Putu Dewi Marlyna (IAI Darussalam, 2026)
Pharmacy signage in Muncar and Cluring Districts represents the dynamics of language competition in the linguistic landscape of public spaces in the developing healthcare sector amidst the competitive service economy. This study aims to identify the forms of language competition that emerge on pharmacy signage and analyze the social and economic factors that influence language choice. The study employed a qualitative sociolinguistic approach with a linguistic landscape case study design. Data were obtained through field observations and documentation of independent private pharmacy signage, with the researcher acting as the primary instrument. The results indicate that all the signage studied falls into the bottom-up sign category because it was created at the initiative of the business owner. The findings also show that pharmacy signage in Muncar District is dominated by bilingual forms combining Arabic, Javanese, and Indonesian, while in Cluring District, Indonesian is predominantly used monolingually. The use of language variations in Muncar serves to build a religious image and strengthen closeness to local identity, while the dominance of Indonesian in Cluring is oriented towards aspects of understandability, readability, and ease of access to information for the public. This study concludes that pharmacy signage not only serves as a marker of business identity but also serves as a medium for linguistic competition, reflecting the construction of social identity and economic marketing strategies through the use of language as symbolic capital and a commodity to enhance business competitiveness.